2009
DOI: 10.1111/j.1553-2712.2009.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Undiagnosed Diabetes and Prediabetic States in High‐risk Emergency Department Patients

Abstract: Background: Diabetes is often not diagnosed until complications appear, and one-third of those with diabetes may be undiagnosed. Prediabetes and diabetes are conditions in which early detection would be appropriate, because the duration of hyperglycemia is a predictor of adverse outcomes, and there are effective interventions to prevent disease progression and to reduce complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 23 publications
4
39
1
Order By: Relevance
“…In our sample, 22.5 % of adult patients who were treated at the ED met the DM criteria and another 5.9 % met the criteria for newly diagnosed DM. This finding is consistent with previous studies [7, 18, 19]. HbA1c levels are also an indicator of future DM and may be useful for defining personalized prevention strategies [20].…”
Section: Discussionsupporting
confidence: 93%
“…In our sample, 22.5 % of adult patients who were treated at the ED met the DM criteria and another 5.9 % met the criteria for newly diagnosed DM. This finding is consistent with previous studies [7, 18, 19]. HbA1c levels are also an indicator of future DM and may be useful for defining personalized prevention strategies [20].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with unequivocal signs of hyperglycemia such as polyuria, polydipsia, nocturia, or acidosis are likely to need hospital admission, where further testing may be performed. Using an insulin protocol, treatment of hyperglycemia should ideally begin before admission and should not be delayed by confirmatory testing 42 . This requires close and clear communication and collaboration between the Emergency Physician and the Hospitalist.…”
Section: Emergency Department Evaluation Of Hyperglycemia and Hypoglymentioning
confidence: 99%
“…A prospective cohort study conducted in an urban emergency department found that all patients with risk factors for diabetes (age greater than 45 years, polyuria, and polydipsia) and a random blood glucose greater than 155 mg/dl were later diagnosed with pre-diabetes or diabetes 42 . The use of A 1 C as a screening tool in emergency departments is being studied 38 but is not currently recommended 41 .…”
Section: Emergency Department Evaluation Of Hyperglycemia and Hypoglymentioning
confidence: 99%
“…In the ED setting, a few reports have described screening using random BG and/or A1C for detecting undiagnosed DM and/or prediabetes. Charfen and colleagues found that subjects with two DM risk factors and a random BG >155 mg/dl all had DM or pre-DM on follow-up testing 5 . In another study, 51% of patients in the ED were found to have borderline (5.5-6.0%) and 29% abnormal (≥6.1%) A1C results.…”
mentioning
confidence: 99%